Doktor Maciej Kłodawski i jego wkład w teorię praw - Beata Kanarek (Acta Iuris Stetinensis, 2023)
The article is an attempt to characterize scientific achievements of the late Maciej Bogusław Kłodawski, PhD (1985–2020), an outstanding legal theorist who died prematurely, in particular an expert on the technical side of lawmaking. Out of necessity, the content of the article was formulated on the basis of secondary data involving a review and critical analysis of M. Kłodawski’s works. The scientific achievements of M. Kłodawski, apart from the monograph entitled Redundancja w tekście prawnym (Redundancy in the legal text, Toruń 2017) includes thirteen scientific articles published in scientific journals and collective works, four co-authored articles and three works of which M. Kłodawski was an editor or co-editor. The article presents the main fields of research by M. Kłodawski, starting from the structure and content of the legal text, through detailed issues related to the subject of good legislative practice, to the use of artificial intelligence in law. The analysis of dr Kłodawski’s scholarly achievements allows a claim that his contribution into legal theory, especially the part that concerns law-making, is indisputable.